FAKTOR-FAKTOR YANG MEMPENGARUHI MAHASISWA DALAM MENENTUKAN MATA KULIAH PILIHAN DI JURUSAN ILMU KESEJAHTERAAN KELUARGA FPP UNP - Syafriani, Selly; Ernawati, Ernawati; Novrita, Sri Zulfia (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The problem in this study is that students do not choose the elective courses based on the level of skills they want to achieve, the students do not consult the academic advisor's lecturer before taking the elective course and it is not clear what factors influence the students in taking the decision to take the elective course. This study aims to describe the factors that affect students in determining the elective courses in the Department of Family Welfare FPP-UNP. This research is descriptive quantitative. The population in this study are students of the family welfare education program year 2013-2014. The sample in this study is the entire population is sampled (total sampling) amounted to 58 people. The data obtained is the primary data obtained from the questionnaire. Data analysis in this research using descriptive analysis technique percentage. Result of research about internal factor from physiological aspect that is 65,52%, psychology aspect 58,28% consisting of intelligence 74,14%, interest 70,69%, talent 67,24%, motivation 55,17% and attitude with percentage of 24.14%. The indicator of the external factor from the aspect of the social environment that is 69,54% which consist of learning approach 84,48%, lecturer PA 68,97%, the impulse of parent 55,17%. The non-social environment aspect is 64,37% which consist of learning tool 81,03%, study time 60,34 and temperature condition with percentage 51,72%.Keywords: Physiological, psychological, social environment, non-social environment